2016
DOI: 10.1002/jbmr.3030
|View full text |Cite
|
Sign up to set email alerts
|

Risk and Prevention of Fracture in Patients With Major Medical Illnesses: A Mini-Review

Abstract: Patients with several medical conditions, including Parkinson's disease, recent stroke, HIV, and heart failure, have a high risk of hip fracture. These patients will also have more severe consequences of a hip fracture, including a greater chance of dying and more prolonged disability. Together, there are nearly as many patients with medical conditions that substantially increase the risk of hip fracture as there are people with osteoporosis by femoral neck bone mineral density (BMD). The contributions of fall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 27 publications
0
18
0
3
Order By: Relevance
“…However, many studies examining the association of potential risk factors with incidence of disease‐related clinical outcomes in the geriatric population often do not take into account the competing risk of death, which can lead to overestimates of incidence of these disease events in this population, particularly if the competing risk of mortality is high. It has previously been suggested that older women with dementia may be at high risk of hip fracture and should be targeted for drug treatment to lower fracture risk . However, our results highlight the importance of consideration of the competing risk of mortality when evaluating potential risk factors such as cognitive impairment as predictors of hip fracture in older adults.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…However, many studies examining the association of potential risk factors with incidence of disease‐related clinical outcomes in the geriatric population often do not take into account the competing risk of death, which can lead to overestimates of incidence of these disease events in this population, particularly if the competing risk of mortality is high. It has previously been suggested that older women with dementia may be at high risk of hip fracture and should be targeted for drug treatment to lower fracture risk . However, our results highlight the importance of consideration of the competing risk of mortality when evaluating potential risk factors such as cognitive impairment as predictors of hip fracture in older adults.…”
Section: Discussionmentioning
confidence: 63%
“…It has previously been suggested that older women with dementia may be at high risk of hip fracture and should be targeted for drug treatment to lower fracture risk. (8) However, our results highlight the importance of consideration of the competing risk of mortality when evaluating potential risk factors such as cognitive impairment as predictors of hip fracture in older adults.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The baseline comorbidities and use of medications which were considered as possible potential confounders (listed in table 1) were selected according to previous studies. [42][43][44][45][46][47][48] The criteria for defining pre-existing comorbidity was the positive diagnosis of any disease either at the time of a minimum of one hospital admission or two outpatient visits within the year prior to the index date. A baseline use of medication was defined as the use of these drugs at least 30 days during the year preceding the index date.…”
Section: Primary Outcomementioning
confidence: 99%